Data of pluviographic observations of rainfall at weather stations of the Urals (1936-2015) - Dmitriy Klimenko; Dariya Kutergina (PANGAEA, 2020)
The database is an array of minute resolution observations over the rainfall of weather stations of the Urals (Russia). The database contains observational data on pluviographs at 79 meteorological stations located in the regions of the Russian Federation: Sverdlovsk region; Perm Territory; Chelyabinsk region; Kurgan region. The period for which the data is placed is from 1936 to 2015.